Improving Surveillance for Surgical Site Infections Following Total Hip and Knee Arthroplasty Using Diagnosis and Procedure Codes in a Provincial Surveillance Network. (28th March 2016) - Rusk, Alysha; Bush, Kathryn; Brandt, Marlene; Smith, Christopher; Howatt, Andrea; Chow, Blanda; Henderson, Elizabeth
Abstract : OBJECTIVE: To evaluate hospital administrative data to identify potential surgical site infections (SSIs) following primary elective total hip or knee arthroplasty. DESIGN: Retrospective cohort study. SETTING: All acute care facilities in Alberta, Canada. METHODS: Diagnosis and procedure codes for 6 months following total hip or knee arthroplasty were used to identify potential SSI cases. Medical charts of patients with potential SSIs were reviewed by an infection control professional at the acute care facility where the patient was identified with a diagnosis or procedure code. For SSI decision, infection control professionals used the National Healthcare Safety Network SSI definition. The performance of traditional surveillance methods and administrative data–triggered medical chart review was assessed. RESULTS: Of the 162 patients identified by diagnosis or procedure code, 46 (28%) were confirmed as an SSI by an infection control professional. More SSIs were identified following total hip vs total knee arthroplasty (42% vs16%). Of 46 confirmed SSI cases, 20 (43%) were identified at an acute care facility different than their procedure facility. Administrative data–triggered medical chart review with infection control professional confirmation resulted in a 1.1- to 1.7-fold increase in SSI rate compared with traditional surveillance. SSIs identified by administrative data resulted in sensitivity of 90% and specificity of 99%. CONCLUSION: Medical chart review for cases identified through administrative data is an efficient supplemental SSI surveillance strategy. It improves case-finding by increasing SSI identification and making identification consistent across facilities, and in a provincial surveillance network it identifies SSIs presenting at nonprocedure facilities. Infect Control Hosp Epidemiol 2016;37:699–703